ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI DAN PARTISIPASI WARGA BELAJAR DI SKB KOTA BINJAI - Kaniwa Silvyani; Sonya Letare Nababan; Teovilla Grace Natasia Br Ginting; Esra haniarta Saragih; Esabella Sinaga; Alvin telaumbanua (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the factors affecting learners’ motivation and participation, and to formulate strategies to optimize learning outcomes at the Nonformal Education Center (SKB) in Binjai City. The study is based on the phenomenon of low learning motivation characterized by fluctuating attendance, passive participation, and a focus on certification rather than meaningful learning. This indicates a gap between the objectives of nonformal education and its actual practice. A qualitative descriptive approach was used, employing semi-structured interviews, participatory observation, and documentation. Data were analyzed interactively through data reduction, display, and conclusion drawing. The findings reveal that low motivation stems from both internal factors (low interest, lack of self-confidence, narrow learning goals) and external factors (limited facilities, monotonous methods, minimal social support). These factors result in low participation, poor learning outcomes, and weak lifelong learning orientation. Increasing motivation can be achieved through effective group communication, participatory learning methods, and supportive learning environments.